Multicultual World and its Challenges - Mesić, Milan, sociolog (Array, 2009)
The recent emergence of multiculturalism (and interculturalism) can be explained as a (theoretical, political, ideological) respond to multiculturality of contemporary societies, on the one hand, and as a reaction to centuries long dominance of a worldview that may be denoted as monoculturalism. However, there is no simple, widely shared definition of multiculturalism. It is a vague and at the same time fiercely contested term. There are deep both political and theoretical divisions not only between its advocates and critics, but even between the two theoretical and ideological camps. The author concludes that the challenges of multicultural world are here to stay for some time in the future.